2020
DOI: 10.1177/1464884920958367
|View full text |Cite
|
Sign up to set email alerts
|

How to report on elections? The effects of game, issue and negative coverage on reader engagement and incivility

Abstract: This study investigates to what extent specific features of news articles about election campaigns impact reader engagement and civility in news comments. Using content analysis of articles ( N = 830) and comments ( N = 29,421) published during the 2015 Portuguese Legislative elections, we test the impact of negative coverage, issue coverage and game coverage (politics as a game) on the number of comments that an article receives and the level of civility thereof. Additionally, we explore how affective polaris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 54 publications
2
5
1
2
Order By: Relevance
“…Results of the content analysis of user comments on the website and the Facebook page of the Austrian daily newspaper Der Standard show that nearly every third of the comments analyzed contained incivility. Levels of incivility in the online discussions on COVID-19 found in this study are comparable to those found in prior studies on various other topics which ranged between 20 and 40% (Coe et al, 2014;Santana, 2014;Rowe, 2015a;Su et al, 2018;Gonçalves et al, 2020;Rossini, 2020). Despite its polarizing character, topics related to COVID-19 do not seem to generate higher levels of incivility compared to other topics.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Results of the content analysis of user comments on the website and the Facebook page of the Austrian daily newspaper Der Standard show that nearly every third of the comments analyzed contained incivility. Levels of incivility in the online discussions on COVID-19 found in this study are comparable to those found in prior studies on various other topics which ranged between 20 and 40% (Coe et al, 2014;Santana, 2014;Rowe, 2015a;Su et al, 2018;Gonçalves et al, 2020;Rossini, 2020). Despite its polarizing character, topics related to COVID-19 do not seem to generate higher levels of incivility compared to other topics.…”
Section: Discussionsupporting
confidence: 82%
“…It is directed against people on the basis of their race, ethnic origin, religion, gender, age, physical condition, disability, sexual orientation, political conviction, and so forth" (p. 900). Prior studies show that around 20-40% of user comments on online news websites are uncivil (Coe et al, 2014;Santana, 2014;Rowe, 2015a;Su et al, 2018;Gonçalves et al, 2020;Rossini, 2020). These studies indicate that comments on articles on highly controversial topics such as same-sex marriage or immigration show higher levels of incivility compared to other articles.…”
Section: Literature Review and Research Questions Incivility In Onlin...mentioning
confidence: 99%
“…Relevant to this study, Facebook pages of news media might be well suited to provide a platform for quality discussions (Ziegele et al, 2020), given that debate coverage on Facebook can lead to user conversations that exhibit elements of rational discourse (Camaj, 2021). However, this line of research has been criticized for its predominant concentration on the negative aspects of online discourses, such as incivility (Gonçalves et al, 2022) or toxicity (Ventura et al, 2021), often at the expense of the constructiveness and other positive aspects of the online comments (Reimer et al, 2023).…”
Section: The Democratic Function Of Online Discussion During Politica...mentioning
confidence: 99%
“…News coverage about political candidates is pivotal for the electorate to form their informed decisions. However, journalists and editors during hectic campaign seasons can be overwhelmed with a multitude of choices to make—some may focus on the most important issues the country faces, some may devote to highlighting the candidates and their families, and yet others can pursue the horse race and treat the election like a game among the vying candidates (Gonçalves et al, 2022). In most democracies, horse race has gradually been focused more in election stories since the late 1970s (Broh, 1977; Sinclair, 1982), even though the prestigious press was still found to cover important issues facing the nation or communities.…”
Section: Literature Reviewmentioning
confidence: 99%